The effect of breakfast composition and energy contribution on cognitive and academic performance: a systematic review. Issue 2 (27th May 2014) - Edefonti, Valeria; Rosato, Valentina; Parpinel, Maria; Nebbia, Gabriella; Fiorica, Lorenzo; Fossali, Emilio; Ferraroni, Monica; Decarli, Adriano; Agostoni, Carlo
ABSTRACT: Background: Most studies that assess the effects of breakfast on subsequent mental abilities compared performance in subjects who had or had not consumed this meal. However, characteristics of breakfast itself may induce metabolic and hormonal alterations of the gastrointestinal tract and potentially modify cognitive performance. Moreover, as far as the evidence on the positive effects of having breakfast is becoming more robust, interest may shift to the specific characteristics of an adequate breakfast. Objective: The objective was to summarize existing evidence on the role of nutrient composition or energy intake at breakfast on the accomplishment of school-related tasks and cognition. Design: We conducted a systematic review of the literature through the PubMed database. Results: From the literature search, we identified 102 articles, 15 of which met the inclusion criteria. Of these, 3 studies provided information on the relation between cognitive and academic performance and energy intake at breakfast, 11 provided the same information for the macronutrient composition of breakfast, and 1 investigated both the aspects. Eleven studies considered breakfast meals differing in glycemic index/load. Selected studies were generally carried out in well-nourished children and adults of both sexes from general education. They were mostly experimental studies of short duration and had a limited number of subjects. Cognitive and academic performance was investigated by looking at multiple domains, including memory, attention, reasoning, learning, and verbal and math abilities, with a variety of test batteries scheduled at different time points in the morning. Breakfast options differed in terms of included foods and place and time of administration. Conclusions: There is insufficient quantity and consistency among studies to draw firm conclusions. However, whereas the hypothesis of a better and more sustained performance with a breakfast providing >20% daily energy intake still needs substantiation, there does appear to be emerging, but still equivocal, evidence that a lower postprandial glycemic response is beneficial to cognitive performance.